PENYELESAIAN SENGKETA HARTA PERKAWINAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 - Iswantoro, Iswantoro (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
The writing of this article is motivated by the implementation of marriage agreements in Article 147 of the KUHPerdata and Article 29 of Law Number 1 of 1974 about Marriage, which states that marriage agreements are made before the marriage happened. This rule restricts the freedom of two individuals to perform the agreement, so that it is contrary to Article 28 points e paragraph 2 of the 1945 Constitution. In 2015, the Constitutional Court (MK) issued Decision Number: 69 / PUU-XIII / 2015 which concerning about the issue of the marriage agreement. This article discusses the settlement of marital property disputes after the Constitutional Court's decision in terms of normative legal studies. The study focused on legal principles, legal systematics, legal synchronization, and legal history. The result: (1) based on the Constitutional Court's decision, the marriage agreement can be made as long as the marriage bond takes place with mutual agreement witnessed by a notary without having to be preceded by a court ruling; (2) the Constitutional Court's decision results in joint and third party assets that made and witnessed by a notary begins to take effect from the time the marriage takes place, unless otherwise specified in the marriage agreement. That is, if the parties do not determine when the marriage agreement will take effect, the marriage agreement will take effect from the time the marriage takes place. [Penulisan artikel ini dilatarbelakangi oleh pelaksanaan perjanjian perkawinan dalam Pasal 147 Kitab Undang-undang Hukum Perdata (KUHPerdata) dan Pasal 29 Undang-Undang Nomor 1 tahun 1974 tentang Perkawinan, yang menyebutkan bahwa perjanjian perkawinan dibuat sebelum perkawinan dilangsungkan. Peraturan ini membatasi kebebasan dua orang individu untuk melakukan perjanjian, sehingga bertentangan dengan Pasal 28 Poin e Ayat 2 Undang-Undang Dasar 1945. Tahun 2015, Mahkamah Konstitusi (MK) mengeluarkan Putusan Nomor: 69/PUU-XIII/2015 yang di antara ketentuannya menyangkut persoalan perjanjian perkawinan. Artikel ini membahas penyelesaian sengketa harta perkawinan pasca putusan MK tersebut dari sisi kajian hukum normatif. Kajian difokuskan pada asas-asas hukum, sistematika hukum, sinkronisasi hukum, dan sejarah hukum. Hasilnya: (1) berdasarkan pada putusan MK tersebut, perjanjian perkawinan dapat dibuat selama ikatan perkawinan berlangsung atas persetujuan bersama di depan notaris tanpa harus didahului oleh penetapan pengadilan; (2) putusan MK tersebut berakibat pada harta bersama dan pihak ketiga yang dibuat di hadapan notaris mulai berlakunya sejak perkawinan dilangsungkan, kecuali ditentukan lain dalam perjanjian perkawinan. Artinya, apabila para pihak tidak menentukan kapan perjanjian perkawinan tersebut mulai berlaku, maka perjanjian perkawinan tersebut berlaku sejak perkawinan dilangsungkan.]